Review—Meta-Review of Fire Safety of Lithium-Ion Batteries: Industry Challenges and Research Contributions. Issue 9 (17th August 2020) - Bravo Diaz, Laura; He, Xuanze; Hu, Zhenwen; Restuccia, Francesco; Marinescu, Monica; Barreras, Jorge Varela; Patel, Yatish; Offer, Gregory; Rein, Guillermo
Abstract : The Lithium-ion battery (LIB) is an important technology for the present and future of energy storage, transport, and consumer electronics. However, many LIB types display a tendency to ignite or release gases. Although statistically rare, LIB fires pose hazards which are significantly different to other fire hazards in terms of initiation route, rate of spread, duration, toxicity, and suppression. For the first time, this paper collects and analyses the safety challenges faced by LIB industries across sectors, and compares them to the research contributions found in all the review papers in the field. The comparison identifies knowledge gaps and opportunities going forward. Industry and research efforts agree on the importance of understanding thermal runaway at the component and cell scales, and on the importance of developing prevention technologies. But much less research attention has been given to safety at the module and pack scales, or to other fire protection layers, such as compartmentation, detection or suppression. In order to close the gaps found and accelerate the arrival of new LIB safety solutions, we recommend closer collaborations between the battery and fire safety communities, which, supported by the major industries, could drive improvements, integration and harmonization of LIB safety across sectors.